From Alliance to Estrangement: A Historical Study of Mughal–Rajput Political and Cultural Relations - Chamoli, Amit; Gothwal, Ravinder (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Mughal–Rajput relationship occupies a central place in the political and cultural history of North India. The early alliance, especially under Akbar, fostered administrative stability and cultural integration. However, after the death of Aurangzeb in 1707, this relationship began to transform. The decline of Mughal authority encouraged the Rajputs to renegotiate their political strategies, often asserting greater autonomy or aligning with emerging powers such as the Marathas and later the British East India Company. This study examines these shifts in power relations from 1707 to 1948, highlighting how the decline of imperial authority, regional rivalries, and colonial interventions altered the nature of Mughal–Rajput interactions. Alongside politics, the paper also explores the cultural dimensions of this relationship, including matrimonial ties, courtly traditions, architectural patronage, and religious policies, which served as mechanisms of both diplomacy and identity construction. With the advent of British colonialism, Rajput states adapted to new forms of governance and became central actors within the princely state system under indirect rule. By employing a historical-analytical perspective, the study demonstrates that the Mughal–Rajput bond was not a simple narrative of harmony or hostility, but a complex, evolving process of cooperation, contestation, and adaptation. Ultimately, it sheds light on how these interactions influenced Indo-Islamic cultural exchanges and shaped political developments in India leading up to independence.